Optimization and Optimal Control Theory and Applications - Chinchuluun, Altannar; Pardalos, Panos M.; Enkhbat, Rentsen; Tseveendorj, Ider.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Optimization and optimal control are the main tools in decision making. Because of their numerous applications in various disciplines, research in these areas is accelerating at a rapid pace. "Optimization and Optimal Control: Theory and Applications" brings together the latest developments in these areas of research as well as presents applications of these results to a wide range of real-world problems. The book is composed of invited contributions by experts from around the world who work with optimization and optimal control either at a theoretical level or in practice. Some key topics presented include: equilibrium problems, stochastic processes, decision algorithms, scheduling, queuing theory, quantum computing, agriculture, and industrial operations. This volume can serve as a useful resource for researchers, practitioners, and advanced graduate students of mathematics and engineering working in research areas where results in optimization and optimal control can be applied.
Sensibility Function as Convolution of System of Optimization Problems -- Post-Optimal Analysis of Linear Semi-Infinite Programs -- On Equilibrium Problems -- Scalarly Compactness, (S)+-Type Conditions, Variational Inequalities and Complementarity Problems in Banach Spaces -- Quasi-equilibrium Inclusion Problems of the Blum-Oettli-Type and Related Problems -- General Quadratic Programming and Its Applications in Response Surface Analysis -- Canonical Dual Solutions for Fixed Cost Quadratic Programs -- Algorithms of Quasidifferentiable Optimization for the Separation of Point Sets -- A Hybrid Evolutionary Algorithm for Global Optimization -- Gap Functions for Vector Equilibrium Problems via Conjugate Duality -- Polynomially Solvable Cases of Binary Quadratic Programs -- Generalized Solutions of Multi-valued Monotone Quasi-variational Inequalities -- Optimal Feedback Control for Stochastic Impulsive Linear Systems Subject to Poisson Processes -- Analysis of Differential Inclusions: Feedback Control Method -- A Game Theoretic Algorithm to Solve Riccati and Hamilton-Jacobi-Bellman-Isaacs (HJBI) Equations in H ? Control -- Online Adaptive Optimal Control Based on Reinforcement Learning -- Perturbation Methods in Optimal Control Problems -- Stochastic Optimal Control with Applications in Financial Engineering -- A Nonlinear Optimal Control Approach to Process Scheduling -- Hadamard's Matrices, Grothendieck's Constant, and Root Two -- On the Pasture Territories Covering Maximal Grass -- On Solvability of the Rate Control Problem in Wired-cum-Wireless Networks -- Integer Programming of Biclustering Based on Graph Models -- A Random Arrival Time Best-Choice Problem with Uniform Prior on the Number of Arrivals.
Keywords: MATHEMATICS; MATHEMATICAL OPTIMIZATION; MATHEMATICS; CALCULUS OF VARIATIONS AND OPTIMAL CONTROL; OPTIMIZATION; MATHEMATICAL MODELING AND INDUSTRIAL MATHEMATICS; OPERATIONS RESEARCH, MANAGEMENT SCIENCE